2019
DOI: 10.3390/ijms20112771
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profile Analysis of Winter Rapeseed (Brassica napus L.) in Response to Freezing Stress, Reveal Potentially Connected Events to Freezing Stress

Abstract: Winter rapeseed is not only an important oilseed crop, but also a winter cover crop in Northern China, where its production was severely limited by freezing stress. As an overwinter crop, the production is severely limited by freezing stress. Therefore, understanding the physiological and molecular mechanism of winter rapeseed (Brassica napus L.) in freezing stress responses becomes essential for the improvement and development of freezing-tolerant varieties of Brassica napus. In this study, morphological, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 100 publications
(116 reference statements)
8
37
0
Order By: Relevance
“…This result showed that ROS induced lipid peroxidation and the level of injury depended on the cold-resistant properties of the cultivars. Our findings are in agreement with previous study that cold-tolerant species, such as Santalum album (Zhang et al, 2017), Vitis amurensis (Xu et al, 2014), Solanum lycopersicum (Chen et al, 2015), B. rape (Ma et al, 2019), and B. napus (Pu et al, 2019a) have strong protective enzyme activity and high content of soluble regulators which can reduce ROS production. The present physiochemical study confirmed that cultivar 16NTS309 had significantly higher cold resistance than cultivar Tianyou2238.…”
Section: Physiochemical Changes Of Winter B Napus After Cold Stresssupporting
confidence: 94%
See 1 more Smart Citation
“…This result showed that ROS induced lipid peroxidation and the level of injury depended on the cold-resistant properties of the cultivars. Our findings are in agreement with previous study that cold-tolerant species, such as Santalum album (Zhang et al, 2017), Vitis amurensis (Xu et al, 2014), Solanum lycopersicum (Chen et al, 2015), B. rape (Ma et al, 2019), and B. napus (Pu et al, 2019a) have strong protective enzyme activity and high content of soluble regulators which can reduce ROS production. The present physiochemical study confirmed that cultivar 16NTS309 had significantly higher cold resistance than cultivar Tianyou2238.…”
Section: Physiochemical Changes Of Winter B Napus After Cold Stresssupporting
confidence: 94%
“…In the present study, more obvious ultrastructural alterations in leaf mesophyll including the damage of membrane system, destruction of chloroplast and swelling of mitochondria were observed in cold-sensitive variety of Tianyou2238 compared to cold-resistant cultivar 16NTS309. Similar damage in the leaf mesophyll cell ultrastructures was investigated in B. napus against cold stress ( Stefanowska et al., 2002 ; Pu et al., 2019a ). Previous research reported that chloroplasts are thought to be the first and most severely affected organelle ( Kratsch and Wise, 2000 ), and cold stress may lead to unstacking of grana and disintegration of the chloroplast envelope ( Klein, 1960 ; Kislyuk, 1963 ; Jagels, 1970 ; Taylor and Craig, 1971 ; Murphy and Wilson, 1981 ; Kratsch and Wise, 2000 ; Vella et al., 2012 ).…”
Section: Discussionmentioning
confidence: 87%
“…Relative electrolyte leakage was regarded as the direct marker to reflect the membrane damage by freezing stress in previous studies (Campos et al, 2003;Pu et al, 2019). According to the relative electrolyte leakage and the damage level of seedling ( Supplementary Figure S1), we selected leaves treated 4 h at −6 • C to conduct RNA extraction and transcriptome sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptome sequencing has been proven to be an efficient method for cold-related gene discovery, which has been studied extensively in Arabidopsis (Lee et al, 2005) and cereal crops such as rice (Zhang et al, 2012), maize (Trzcinska-Danielewicz et al, 2009), barley (Tommasini et al, 2008), and wheat (Gulick et al, 2005). RNA-seq has discovered several cold-related pathways and a series of key coldresponsive genes (Laudencia-Chingcuanco et al, 2011;Pu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we detected one BRI1 gene and 12 TCH4 genes predominantly expressed in T24 and found that most genes in the BR signaling pathway were exclusively present in the blue module, indicating that BR signaling was necessary for cotyledon cold tolerance. Additionally, some studies have demonstrated that genes involved in the auxin signaling pathway are differentially expressed when plants are subjected to cold stress [30,69]. In these remarkable modules, we identified 136 genes involved in plant hormone signaling pathway, of which 46 were related to auxin signal transduction, most of which were from the blue module, indicating that auxin played a significant role in regulating cotyledon cold tolerance.…”
Section: Genes Related To Phytohormone Signal Transduction Involved Imentioning
confidence: 93%